Awareness on Immunity Boosting Measures for Self-care among Residents of Urban Community of Pune City - Sheela Upendra (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Ministry of Ayush applauds guidelines for immunity boosting measures for self-care toenhance immunity with special reference to respiratory health of individual. These guidelines are supportedby Ayurveda literature and scientific publications. To maintain the optimum health it is very important toenhance the body’s natural defense system i.e immunity of individual Objective :To assess the Immunityboosting measures for self-care among residents of Urban community and to determine the association ofawareness with selected demographic variables Methods: Quantitative non experimental survey researchdesign was used for the study. Sample size comprised of 100. Non probability convenience samplingtechnique was used for the study. Reliability of the tool was calculated by cronbach’s alpha method andwas 0.802.Tool includes Two sections. Section I included demographic proforma of the sample. It consistedof information on variables like age, gender, Occupation. Education and Religion. Section II was aboutself-administered structured knowledge questionnaire comprised of twenty one questions .After taking theconsent from each samples tool was administered to participants. Result: Majority of respondents haveaverage knowledge ( 49.7% ) , good knowledge (04%) and 46.3% respondents had poor knowledge . Sinceall the p-values are large (greater than 0.05), there is no evidence against null hypothesis. None of thedemographic variable was found to have significant associated with knowledge of the urban communityresidents regarding immunity boosting measures for self care Conclusion: The residents had considerableaverage knowledge regarding Immunity boosting measures for self care. The enhancement in knowledge isgreatly required on Immunity boosting measures for self care